Do lenders price diesel risk? Evidence from Dieselgate and low-emission zones in captive vs. independent banks - Winta Beyene; Matteo Falagiarda; Steven Ongena; Alessandro Scopelliti (Leibniz Institute for Financial Research SAFE, 2026)
Transitioning to a sustainable economy and reducing air pollution hinge on appropriate economic incentives and financing conditions. The auto loan market offers a prime setting, as lenders' credit terms can either discourage or incentivize the purchase of high-pollution vehicles. Using loan-level data, we examine how captive and independent banks adjust lending conditions in response to information and regulatory shocks affecting diesel vehicles. Exploiting the 2015 diesel emissions scandal and the introduction of local circulation restrictions, we show that lending responses differ systematically across lender types, with captive banks tending to weaken, rather than reinforce, the effectiveness of environmental regulation for air pollution.
Keywords: G21; G51; Q53; Q58; 330; Car Loans; Captive Banks; Independent Banks; Diesel Emissions Scandal; Car Circulation Restrictions